Pet, Pest, Profit: Patient! How Attitudes Toward Animals Among Veterinary Students in the Netherlands Differ According to Animal Categories and Student-Related Variables - Angelika V. Dijkstra Klaasse; Monique R. E. Janssens; Daniela C. F. Salvatori (Animals)
Veterinarians are not just animal health professionals; they are also considered animal welfare experts. Animal-directed empathy, the ability to understand and match an animal’s emotional state, is essential for recognizing animal welfare issues. It is therefore a vital competency for veterinarians. The factors that play a role in shaping this empathy are animal, personal, and cultural influences, as well as the categorization of animals based on their benefit or harm to people: pet, pest or profit (used for economic purposes). We conducted a survey among veterinary students in the Netherlands to assess their levels of animal-directed empathy by scoring their attitude toward animals with the “Pet, Pest, Profit Scale”. Analysis of 321 completed surveys revealed that students showed the highest empathy for pets, the second-highest levels for pest animals, and the lowest levels for profit animals. Empathy levels also differed depending on career choice, background, and diet. These findings indicate that categorizing animals influences veterinary students’ empathy levels, which can lead to unrecognized welfare issues, especially for pest and profit animals. It is important to enhance empathy for these categories through targeted educational interventions to help prepare veterinary students for their responsibility as veterinarians, ensuring the welfare of all animals, whether pet, pest or profit.